Home : a novel - Yttrup, Ginny L. (Shiloh Run Press, an imprint of Barbour Publishing, Inc., 2017)
When novelist Melanie Vander finds herself faced with a looming deadline, she decides its time for a bit of distance from the problems at home. But once shes away, she escapes into her own fictional world. When hit with a dose of reality, Melanie must choose whether shell check out completely, or allow her characters to lead her home.